Determination of Polar Pesticides Based on a Modified QuPPe with Liquid Chromatography Coupled to Tandem Mass Spectrometry - Gözde Türköz Bakirci (Journal of Food Quality)
An analytical approach for determining polar pesticides using a Hypercarb column that is based on a modified quick polar pesticide (QuPPe) extraction process combined with liquid chromatography-tandem mass spectrometry (LC-MS/MS) was examined. Maleic hydrazide, glyphosate, glufosinate N-acetyl, glufosinate ammonium, fosetyl Al, ethephon, chlormequat chloride, aminomethyl phosphonic acid N-acetyl, aminomethyl phosphonic acid, cyanuric acid, ethylene thiourea, phosphonic acid, propylene thiourea, and acidified methanol solution were used to extract tomato, wheat, olive, sunflower, and herbal tea samples. The amount of solvent, extraction period, and mobile phases used in the experiment were all changed; the analysis included various stationary phases. The method was validated in five matrices spiked at 0.01 and 0.05 mg/kg in accordance with the EU guidance document SANTE/11312/2021 method performance criteria, using six replicates for each concentration for one individual. The limit of detection and limit of quantification (LOQ) values were determined and found to range from 1.82 to 2.44 and 6.07 to 8.13 mg/kg. For all spike levels studied, the approximate recoveries for the pesticides ranged from 85 to 118%, with RSD values of less than 20%. Plant-origin foods from diverse field experiments were effectively processed using the validated approach. This newly developed analytical process can meet the stringent requirements for plant-origin food analysis.